Design and Development of a Mobile-Based E-Tourism Application for Promoting Tourism Destinations in Lombok - Irwan Prasetya; Mei Lin Chen; Ahmad Fauzi (Lembaga Publikasi Ilmiah Nusantara, 2026)
The advancement of mobile technology has driven digital transformation in the tourism sector, including Lombok Island, which has high tourism potential but still faces limitations in information access and integrated services. This study aims to design and develop a mobile-based e-tourism application to enhance the promotion and accessibility of tourist destinations in Lombok. The research method employs a software engineering approach using the waterfall model, including requirement analysis, system design, implementation, and testing. Data were collected through literature studies and observation of user needs. The results indicate that the developed application provides features such as GPS-based location search, tourism recommendations, multimedia information, and integration with local services. System testing shows good usability and potential to increase tourist visits. In conclusion, mobile-based e-tourism applications can serve as an effective solution to support digital and sustainable tourism promotion in Lombok.